Sexualities in Victorian Britain - Adams, James Eli; Miller, Andrew H., 1964- (Book collections on Project MUSE., 1996)
An introduction to Victorian sexualities and a survey of current critical methods, these essays emphasize the remarkable variety of Victorian sexuality and the intricate particularity of sexual identities that shaped the way the Victorians thought about themselves. This absorbing collection will energize reflection on the complexity of human sexuality and on the many different arrays of meaning that it has generated.